A companion to naturalism - Clark, Kelly James, 1956- (Hoboken : John Wiley & Sons, Inc., 2016)
"Since the turn of the twenty-first century, naturalism has become one of the most prominent philosophical orthodoxies in the Western academy. Yet naturalism is more often assumed than defended. The Blackwell Companion to Naturalism offers a systematic introduction that defines, discusses and defends philosophical naturalism. Essays tackle naturalism's role in existing cultural conversations, from Libertarianism to Confucianism, and provide detailed examinations of philosophical concepts like metaphysics, realism, feminism, science, free will, and ethics as viewed through a naturalist lens. With contributions from an international array of established and emerging scholars from across the humanities, the collection encapsulates contemporary debates in the field. The Blackwell Companion to Naturalism provides an enlightening and accessible guide for self-identified naturalists and philosophy students who are new to naturalism alike"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Naturalism; PHILOSOPHY / Metaphysics; Naturalism; Electronic books